2014
DOI: 10.2215/cjn.02310213
|View full text |Cite
|
Sign up to set email alerts
|

Association between GFR Estimated by Multiple Methods at Dialysis Commencement and Patient Survival

Abstract: SummaryBackground and objectives The Initiating Dialysis Early and Late study showed that planned early or late initiation of dialysis, based on the Cockcroft and Gault estimation of GFR, was associated with identical clinical outcomes. This study examined the association of all-cause mortality with estimated GFR at dialysis commencement, which was determined using multiple formulas.Design, setting, participants, & measurements Initiating Dialysis Early and Late trial participants were stratified into tertiles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 27 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…Indeed, the IDEAL study did not demonstrate any clinical benefit in commencing dialysis at higher levels of eGFR, and the variability in measurement of eGFR in CKD G5 is such that it should not be considered to reliably reflect kidney function. 31 Registry data indicate mean predialysis eGFR varies among countries (approximately 5 ml/min per 1.73 m 2 in Taiwan; average 8.5 in the UK, 7.3 in Australia, 6.4 in New Zealand, 9-10 in Canada and France, and 11 in the US). [32][33][34][35] Generally, current guidelines do not support preemptive dialysis initiation, [36][37][38] although an exception is the 2011 European guideline.…”
Section: Timing and Preparation For Dialysis Initiationmentioning
confidence: 99%
“…Indeed, the IDEAL study did not demonstrate any clinical benefit in commencing dialysis at higher levels of eGFR, and the variability in measurement of eGFR in CKD G5 is such that it should not be considered to reliably reflect kidney function. 31 Registry data indicate mean predialysis eGFR varies among countries (approximately 5 ml/min per 1.73 m 2 in Taiwan; average 8.5 in the UK, 7.3 in Australia, 6.4 in New Zealand, 9-10 in Canada and France, and 11 in the US). [32][33][34][35] Generally, current guidelines do not support preemptive dialysis initiation, [36][37][38] although an exception is the 2011 European guideline.…”
Section: Timing and Preparation For Dialysis Initiationmentioning
confidence: 99%
“…Recently, a randomized controlled trial, the Initiating Dialysis Early and Late (IDEAL) study, demonstrated that a planned early dialysis initiation (eGFR 10 -14 mL/ min/1.73m 2 ) was not associated with improvement in survival or clinical outcomes compared with late dialysis initiation (eGFR 5 -7 mL/min/1.73m 2 ) (18,19).…”
mentioning
confidence: 99%
“…The premise underlying the use of eGFR as an indicator of kidney function in this setting can also be questioned. The method is based on measurements of serum creatinine, which in this setting may be as reflective of muscle mass as of kidney function [25,26], though this issue would relate similarly to those on the dialysis and CKM pathways. The difference in timing of the follow-up eGFR measurement may also be important, since the measurement in those on the CKM pathway was taken nearer to death.…”
Section: Discussionmentioning
confidence: 99%